The relationship between intimate partner violence and cervical cancer screening among women aged 15 and older in South Africa - Hollington, Marcus (My University, 2022)
Background: Cervical cancer is the fourth most prevalent cancer among women globally. In Sub-Saharan Africa, the prevalence of the disease is on the rise with over 74,000 new cases and an estimated 50,000 deaths annually. Moreover, the region constitutes over a third of all cervical cancer fatalities in the world despite representing only 14% of the globe’s female population. In South Africa, it is the second most prevalent cancer. Amidst the disease’s prevalence is the presence of Intimate Partner Violence (IPV) in South Africa, which could impair the ability of women to undergo cervical cancer screening (CSS). Some studies have shown that female victims of IPV are significantly less likely to seek medical assistance for fear of further violence or abandonment by their partners. Thus, illustrating its negative implications on health-seeking behavior. This study examined if, and how, IPV among women aged 15 and older is associated with CCS. Methods: The study used cross-sectional data from the South Africa Demographic and Health Survey conducted in 2016. The population of interest was women aged 15 and older that underwent CCS. The sample size included 1,934 women who responded to the CCS question. The main independent variable was IPV which was developed by combining emotional, severe, less severe, and sexual violence. Thus, women that experienced any one of these forms of IPV fell into the IPV variable. The other independent variables constituted socio-demographic and health/risk factors of cervical cancer. Frequencies were calculated to determine the levels of CCS in South Africa. Bivariate analysis was conducted to investigate the relationship between cervical cancer screening and each of the study’s independent variables. Finally, a binary regression model was used to determine the association between IPV and CCS among women aged 15 and older, whilst controlling for other variables. Results: The study found that 39% of women aged 15 and older have undergone CSS at least once in their lifetime in South Africa. Women that underwent CCS at least once in their lifetime were most common amongst women in the Western Cape (67,38%) followed by women from the North West (42,19%), Northern Cape (40,56%), Eastern Cape (40,26%), Free State (39,18%), Mpumalanga (36,55%), Gauteng (33,65%), Limpopo (33,21%) and KwaZulu-Natal (31,64%). Women from rural areas were less likely to undergo CCS compared to women from urban areas (UOR: 0.63; p<0.05; CI: 0.52-0.76 and AOR: 0.63; p<0.05; CI: 0.48-0.82). Women that experienced intimate partner violence were more likely to undergo CSS compared to women that did not experience intimate partner violence (UOR: 1.33; p<0.05; CI: 1.07-1.65 and AOR: 1.46; p<0.05; CI: 1.14-1.86). Conclusion: The study contributed to our understanding of predictors of CCS in South Africa, particularly the association between IPV and CCS. It found that women that experience IPV are more likely to undergo CCS compared to women that do not experience IPV. This is because women that experience IPV are at greater risk of contracting cervical cancer. Thus, their need to undergo CCS. This highlights the severity of IPV in South Africa and the health risks it poses to women particularly when it comes to cervical cancer. To this end, policymakers related stakeholders should put in place measures that protect women from IPV as well as increase their access to pap smear tests on a regular basis for women at risk of the disease. Thus, its role should be considered in the development of Cervical Cancer Prevention and Control Policy and other programmes to enhance CCS by addressing the social ill among other predictors.
A research report submitted in partial fulfilment of the requirements for the award of the degree of Master of Arts in Demography and Population Studies, Faculty of Humanities to the School of Social Sciences, University of the Witwatersrand, Johannesburg, 2022